PERENCANAAN PEMBANGUNAN GEDUNG BARU 3 LANTAI “TABEK MAINAN” DI JALAN M.YAMIN KELURAHAN AUR KUNING KECAMATAN AUR BIRUGO TIGO BALEH KOTA BUKITTINGGI - Shinta Andira; Deddy Kurniawan; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The number of buildings that collapsed was caused by the ability of a structure that was not able to support the working load, causing significant loss of property and even life. Therefore, in planning the design of a building structure, it must be really full of accuracy, careful calculations and according to the requirements with reference to the Indonesian National Standard (Indonesian Loading Regulations for Buildings and Buildings SNI-2847-2019 and SNI-1726-2019). This study aims to plan the dimensions of structural elements, calculation of structural reinforcement. The structural element data used are the results of the preliminary design (Preliminary Design). The analysis is assisted by the SAP2000 Version 11 program with the selection of a network system structure system (Grid System). Based on the results of the Preliminary design calculation, data is obtained for the use of the superstructure of the 1st floor to the 3rd floor where the cross section of the main column is 40 x 50 cm, the terrace column is 30x30 cm, the main beam is 30x40 cm, and the joist is 20x30 cm. The planning of floor slabs and also not concrete which was carried out with Preliminary design was found to be 12 cm thick. Planning for the foundation using a well foundation with a depth of 2 meters, and using a concrete buis with a diameter of 1 meterKeywords: Preliminary design, SAP2000 analysis, reinforcement calculation, foundation bearing capacity